EFL Teacher Agency Across Contexts: A Mixed-Methods Study of Instructional Problem-Solving in Urban and Rural Schools - Santi Farmasari; Desi Herayana; Hartati Suryaningsih; La Ode Alfin Aris Munandar; Yusril Aditia (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: EFL teaching in Indonesian urban and rural schools have been experiencing persistent challenges due to linguistic, cultural, geographical and resources differences. However, these conditions have not been portraited from ecological persepctive of agency. Therefore, this study examines EFL teacher agency and instructional problem-solving in urban and rural Indonesian classrooms Methodology: This mixed-method study involves 129 EFL instructors (85 from rural schools, 44 from urban schools) who completed a survey, and 35 submitted reflective journals. Quantitative data were assessed using descriptive statistics, and qualitative data were evaluated through thematic analysis. Findings: Both urban and rural EFL teachers faced similar classroom issues like low motivation, vocabulary gaps, and speaking anxiety, though rural teachers linked them to limited resources and urban teachers to distractions and pressure. Urban teachers showed stronger and more consistent agency, especially in autonomy, professional growth, and future goals, while rural teachers drew on deep personal motivation but were often hindered by local challenges. Conclusion: The study shows that teachers’ ecological past experiences, present conditions, and future goals shaped how they solved problems. Rural teachers relied on local resources and flexible strategies, while urban teachers used creative, student-centered methods to build autonomy and global skills, pointing to the need for context-specific support and policies that empower teacher-led innovation. Originality: This study offers how teacher agency is lived out in the everyday problem-solving of EFL classrooms, not just in teachers’ beliefs or intentions. By comparing rural and urban contexts in Indonesia, it reveals how agency looks different across settings and highlights the creativity and resilience of teachers, especially in resource-challenged schools.